Endoparasites of Food-fish landing from the Calabar River, Cross River State, Nigeria - Ekanem, Albert Philip; Eyo, Victor Oscar; Udoh, James P.; Okon, James Asuquo (Journal of Scientific Research & Reports, 2014)
Aims: To investigate the abundance and prevalence of endoparasites of landed food fishes from the Calabar River, Cross River State and the public health implications to fish consumers. Place and Duration of Study: Weekly fish samples were collected for a period of six months (2012) at Nsidung beach, Nigeria. Methodology: A total of 300 fish specimen were collected from 15 fish species (20 from each species) from local fishermen and transported to the Fish Pathology laboratory, University of Calabar, for identification and examination. Organ squash of some organs (liver, spleen, heart and kidney). Stomach and intestinal scrapes were examined microscopically for parasites. Results: Examination showed an overall prevalence of 60% for Bathygobius soporato, 15% for Chrysichthys nigrodigitatus, 10% for Clarias gariepinus and 25% for Synodontis clarias. The preferred organs for Parasite infection were the stomach and intestines of affected fish. Nematodes, trematodes and cestodes were found in decreasing order of abundance. Camallanus kirandensis (nematoda) was found in the intestines and stomach of B. soporato, S. clarias, C. nigrodigitatus and C. gariepinus. Clinostomum complanatum (trematoda) in the stomach and intestine of B. soporato; Diphyllobothrium latum (Cestoda) in the stomach of C. nigrodigitatus; Pomporhynchus laevis (acanthocephala) in the intestine of B. soporato, S. clarias and C. nigrodigitatus and in the stomach of S. clarias. Conclusion: It was concluded that B. soporato, C. nigrodigitatus, C. gariepinus and S. clarias from the Calabar River, landed at Nsidung beach are susceptible to helminth infection and it is recommended that all fish be properly cooked or roasted before consumption to guard against possible human infection by some parasites.
Keywords: Endoparasites; fish; calabar river; public health; prevalence; abundance.